Scrub typhus Meningoencephalitis : Diagnostic dilemma - Narkhede, Nilima; Weling, Rajaram; Prajapati, Sanjay (Nepal Journal of Neuroscience, 2023)
Background: Neurological involvement in the form of meningitis or meningoencephalitis, although well documented in scrub typhus, has not been extensively studied in the pediatric population. It is seldom considered in the differential diagnosis of meningitis in the Indian subcontinent. Case Presentation: We report a case of Scrub typhus meningitis in 13year old male child. The Cerebrospinal Fluid (CSF) revealed lymphocytic pleocytosis, raised proteins and a normal glucose level. Conclusion : Early diagnosis and prompt institution of doxycycline therapy may lead to early cure of scrub typhus even when features of meningitis supervene. However, Ceftriaxone which is commonly used to treat bacterial meningitis is suboptimal in the treatment of scrub typhus. Key words : Scrub typhus, Meningoencephalitis, CSF